Suppression of phenotype of Escherichia coli mutant defective in farnesyl diphosphate synthase by overexpression of gene for octaprenyl diphosphate synthase. Issue 6 (3rd June 2018) - Takahashi, Hiroshi; Aihara, Yuta; Ogawa, Yukihiro; Murata, Yoshimitsu; Nakajima, Ken-ichi; Iida, Maiko; Shirai, Miyako; Fujisaki, Shingo
Abstract: We investigated suppression of the slow growth of an Escherichia coli ispA null mutant lacking farnesyl diphosphate (FPP) synthase (i.e. IspA) by plasmids carrying prenyl diphosphate synthase genes. The growth rates of ispA mutant-transformants harboring a medium-copy number plasmid that carries ispA or ispB were almost the same as that of the wild-type strain. Although the level of FPP in the transformant with the ispA plasmid was almost the same as that in the wild-type strain, the level in the transformant with the ispB plasmid was as low as that in the ispA mutant. Purified octaprenyl diphosphate synthase (IspB) could condense isopentenyl diphosphate (IPP) with dimethylallyl diphosphate (DMAPP) to form octaprenyl diphosphate and nonaprenyl diphosphate. It is possible that suppression of the slow growth of the ispA mutant by ispB was due to condensation of IPP not only with FPP but also with DMAPP by octaprenyl diphosphate synthase. Graphical abstract: : Overexpression of ispB encoding octaprenyl diphosphate synthase suppressed the phenotype of E. coli null mutant ispA encoding farnesyl diphosphate synthase.